Quantitative Pupillometry in the Intensive Care Unit. (April 2021) - Bower, Matthew M.; Sweidan, Alexander J.; Xu, Jordan C.; Stern-Nezer, Sara; Yu, Wengui; Groysman, Leonid I.
Quantitative pupillometry provides a noninvasive and objective assessment within the neurological examination. This review details the physiology of the pupillary light response, the clinical significance of changes in pupillary reactivity, and the variables that compose the Neurological Pupil index or NPi are discussed. This article reviews the most recent applications and advances in quantitative pupillometry for noninvasive intracranial pressure monitoring, postcardiac arrest prognostication, and subarachnoid hemorrhage. Also discussed are the limitations and confounders of quantitative pupillometry in the modern neurological intensive care unit.